Increasing the Productivity of Fried Shallot "Emak" Kediri MSMEs with Appropriate Technology and Business Management Assistance - Riswan Eko Wahyu Susanto; Agus Dani; Yohan Bahtiar; Miftakhul Huda; Setiyo Rojikin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The grand harvest of shallots is a time when almost all shallot farmers harvest simultaneously, resulting in an abundant supply of shallots and a plentiful supply of fried shallot ingredients at low prices. In contrast, during the lean season, shallot prices become expensive, leading to inflation (price fluctuations of shallots). This has a direct impact on the ‘Emak’ Fried Shallots MSMEs located in Kediri Regency. Another problem faced by partners is that the production process is carried out using small-capacity machines, and premium fried shallots are produced manually, so the production process requires a lot of labour, time and production costs. With the implementation of PKM and the application of Appropriate Technology (red onion/shallot slicing machine), it is hoped that the production process can be accelerated and the output of MSMEs increased. The tangible results have been delivered in the form of two Appropriate Technology machines to MSME partners, for the production of premium and Grade A/B/C fried shallots, with a production increase of 10 minutes per kg and a daily production of 40 kg. Based on data from the Fried Shallots MSMEs, the average profit increase over three months reached 118.04% (equivalent to 14.36 million rupiah). The highest profit increase was achieved in September 2024, reaching 125% (equivalent to 15.9 million rupiah). The lowest value in October 2024 reached 80.51% (equivalent to 12.26 million rupiah). This difference in value was mainly due to the fluctuating price of shallots as a raw material and market demand, which increased when prices fell and decreased when the price of fried shallots rose, thereby affecting the profits of MSMEs.